Cashing out : the flight of Nazi treasure, 1945-1948 - Lochery, Neill (PublicAffairs, 2023)
"When Nazis looked to flee Europe with stolen art, gems, and gold in tow, certain "neutral" countries were all too willing to assist them. By the end of January 1945, it was clear to Germany that the war was lost. The Third Reich was in freefall, and its leaders, apart from those clustered around Hitler in his Berlin bunker, sought to abscond before they were besieged. But they wanted to take their wealth with them. Their escape routes were diverse: Sweden and Switzerland boasted proximity, banking, and industrial closeness, while Spain and Portugal offered an inviting Atlantic coastline and shipping routes to South America. And in various ways, each of these so-called neutral nations welcomed the Nazi escapees, along with the clandestine wealth they carried. Cashing Out tells the riveting history of the race to intercept the stolen assets before they disappeared, and before the will to punish Germany was replaced by the political considerations of the fast-approaching Cold War. Bestselling author Neill Lochery here brilliantly recounts the flight of the Nazi-looted riches--the last great escape of World War II--and the Allied quest for justice"--